1997
DOI: 10.1046/j.1471-4159.1997.68030961.x
|View full text |Cite
|
Sign up to set email alerts
|

Defective Herpes Simplex Virus Vectors Expressing the Rat Brain Stress‐Inducible Heat Shock Protein 72 Protect Cultured Neurons from Severe Heat Shock

Abstract: Recently, preinduction of the heat shock re-The preferential induction ofhsps during stress amid sponse has been shown to protect CNS neurons under-an overall decrease in protein synthesis suggests a progoing various stressful insults, e.g., heat, ischemia, or tective role for them. As more correlative support for exposure to excitotoxins. However, it is not known which protection, some neurons that mount a strong hsp reof the proteins induced by the heat shock response medi-sponse preferentially survive stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
84
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 120 publications
(89 citation statements)
references
References 2 publications
4
84
1
Order By: Relevance
“…Strategies to attenuate the neurological symptoms of acute injury are of great clinical importance and their development is the subject of major research interest (Harvey et al, 2003). Intrastriatal delivery of Bcl-2, GDNF or Hsp72 with HSV-1 based vectors was previously shown to protect a small percentage of neurons from ischemic death (Linnik et al, 1995;Lawrence et al, 1996;Fink et al, 1997;Wang et al, 1997;Yenari et al, 1998;Antonawich et al, 1999;Harvey et al, 2003), but at least one such vector, caused inflammation and neurotoxicity (Monville et al, 2004). Genome-free HSV-based vectors were constructed (amplicons), and their safety improved by the development of a helper-free delivery system that supports the replication and packaging of co-transfected amplicon DNA (Olschowka et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Strategies to attenuate the neurological symptoms of acute injury are of great clinical importance and their development is the subject of major research interest (Harvey et al, 2003). Intrastriatal delivery of Bcl-2, GDNF or Hsp72 with HSV-1 based vectors was previously shown to protect a small percentage of neurons from ischemic death (Linnik et al, 1995;Lawrence et al, 1996;Fink et al, 1997;Wang et al, 1997;Yenari et al, 1998;Antonawich et al, 1999;Harvey et al, 2003), but at least one such vector, caused inflammation and neurotoxicity (Monville et al, 2004). Genome-free HSV-based vectors were constructed (amplicons), and their safety improved by the development of a helper-free delivery system that supports the replication and packaging of co-transfected amplicon DNA (Olschowka et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, for therapy to be effective, the surviving neurons must retain normal function (Dumas et al, 2001). In most of the aforementioned studies, neuronal function was not examined (Linnik et al, 1995;Lawrence et al, 1996;Fink et al, 1997;Wang et al, 1997;Yenari et al, 1998;Antonawich et al, 1999), and when examined, neurons were found to be dysfunctional (Harvey et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 For the purpose of this investigation, the activity of ␤-galactosidase was used as a marker to confirm stable transduction of cells and subsequent expression of amplicon plasmids. The coincidence of expression of genes driven from the ␣4 and ␣22 promoters has been quantified previously to be >98%, 21 and thus ␤-galactosidase staining was utilized as a marker for infection. The monocistronic control vector used in these studies expresses the ␤-galactosidase reporter gene under the control of the ␣4 promoter (Figure 1b).…”
Section: Viral Vector Infection In the Absence Of An Insultmentioning
confidence: 99%
“…Induction of HSP70 was seen in models of ischemic tolerance (Chen and Simon 1997;Kirino 2002;Yenari et al 1999a), and inhibition of HSP70 led to partial inhibition of tolerance (Kirino 2002). Virally mediated HSP70 overexpression in cultured neurons protected these cells from heat stress (Fink et al 1997). Viral delivery of HSP70 pre-ischemia was neuroprotective in rat models of stroke (Kelly et al 2002;Yenari et al 1998).…”
Section: Introductionmentioning
confidence: 99%